2021
DOI: 10.1111/jerd.12827
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the renewal or the single application of the peroxide gel on the efficacy and tooth sensitivity outcomes of in‐office bleaching—A systematic review and meta‐analysis

Abstract: Objective To answer the question: “Does the peroxide gel application regimen (single application vs. renewal) influence the efficacy and the tooth sensitivity outcomes of in‐office tooth bleaching?” Methods The search was done in Pubmed, Cochrane, LILACS, Scopus, Web of Science, and EMBASE in February 2021 (updated in July 2021). Randomized clinical trials (RCT) comparing the single application vs. the renewal protocols of HP were included. The meta‐analyses were performed for the objective (ΔEab), subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
(194 reference statements)
0
8
0
1
Order By: Relevance
“…Although renewal of bleaching gel during the in-office appointment is indicated by some manufacturers to maintain the reactivity of the bleaching agent (hydrogen peroxide) during the appointment, a recent systematic review and meta-analysis concluded that color change was not impacted by the bleaching gel application regimen (Kury et al, 2022). Know et al, (2013) Research, Society and Development, v. 11, n. 9, e9811931379, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i9.31379 also observed that a single application of 38% hydrogen peroxide for one hour was as effective as exchanges every 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Although renewal of bleaching gel during the in-office appointment is indicated by some manufacturers to maintain the reactivity of the bleaching agent (hydrogen peroxide) during the appointment, a recent systematic review and meta-analysis concluded that color change was not impacted by the bleaching gel application regimen (Kury et al, 2022). Know et al, (2013) Research, Society and Development, v. 11, n. 9, e9811931379, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i9.31379 also observed that a single application of 38% hydrogen peroxide for one hour was as effective as exchanges every 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the intensity (low, mild, and severe) and duration (short-term or long-term) of DH precipitate directly from the peroxide concentrations and exposure times used [ 17 ]. Therefore, the behavior reported [ 36 ] is expected because at-home bleaching gels are three-to-six times less concentrated than those used in IPB [ 1 , 2 , 3 ], and were demonstrated to be less cytotoxic and to penetrate less into the tooth structure [ 6 , 17 ], thereby diminishing potential risks associated with the vitality of pulpal tissues. Despite these promising results, at-home techniques require long exposure times and result in bleaching outcomes that are only similar to those achieved with IPB [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In-office power bleaching (IPB) is considered an ultraconservative and minimally invasive treatment capable of resolving dental discolorations (low to moderate) in as short as one clinical session [ 1 ]. The IPB treatment typically involves three clinical sessions (45 min each; 7 days apart) using hydrogen peroxide-containing bleaching gels (HP, 35% to 45%), in combination with visible light irradiation or not [ 2 ], to promote the attainment of immediate esthetic outcomes. IPB’s underlying mechanism of action revolves around the generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Während der gesamten Einwirkzeit ist sicherzustellen, dass das Bleichmittel auf den Zähnen verbleibt. Umstritten ist, ob ein mehrmaliges Auftragen des Bleaching-Mittels effektiver ist oder ob es ausreichend ist, das Mittel lieber entsprechend gleich lang zu belassen [6]. Schritt 6 Nach der empfohlenen Einwirkzeit ist das Bleaching-Gel jedenfalls gründlich zu entfernen (▶ Abb.…”
Section: Schrittunclassified